Efektivitas Kerja Sama Local Currency Settlement (LCS) dalam Mendukung Stabilitas Perdagangan Intra-ASEAN - Gratiana Manik; Laura Mairenza Efendes; Tia Putri Yundaris; Indri Melati; Wella Dwi Arianti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
High dependence on the United States Dollar (USD) in international transactions has long been a challenge for economic stability in the Southeast Asian region, especially amidst global exchange rate fluctuations and geopolitical tensions. This study aims to analyze the effectiveness of Local Currency Settlement (LCS) cooperation in supporting intra-ASEAN trade stability. The main focus of this study is how local currency mechanisms can mitigate exchange rate risks and strengthen regional economic integration as part of a de-dollarization strategy. The research method used is descriptive qualitative with a literature review approach, relying on secondary data from central bank reports, ASEAN policy documents, and relevant academic literature. The results show that the implementation of the LCS framework, particularly in countries such as Indonesia, Malaysia, and Thailand, has provided more efficient transaction alternatives by reducing double conversion costs. However, its effectiveness still faces challenges such as low awareness among business actors, limited local currency liquidity compared to the USD, and the need for broader cross-border digital payment system integration. These findings imply the need for strengthened synergy between central banks in the ASEAN region and increased literacy for the private sector so that the economic stability benefits of LCS can be optimally achieved. This strategy not only strengthens monetary sovereignty but also encourages a more resilient ASEAN economic integration against external shocks.